POS Tagging of Hindi-English Code Mixed Text from Social Media: Some Machine Learning Experiments - Sequiera, Royal; Choudhury, Monojit; Bali, Kalika (2015 Proceedings of International Conference on NLP, 2015)
We discuss Part-of-Speech(POS) tagging of Hindi-English Code-Mixed(CM) text from social media content. We propose extensions to the existing approaches, we also present a new feature set which addresses the transliteration problem inherent in social media. We achieve an 84% accuracy with the new feature set. We show that the context and joint modelling of language detection and POS tag layers do not help in POS tagging.